Endogenous Credit Cycles - Gu, Chao; Mattesini, Fabrizio; Monnet, Cyril; Wright, Randall (Journal of Political Economy, 2013)
We study models of credit with limited commitment, which implies endogenous borrowing constraints. We show that there are multiple stationary equilibria, as well as nonstationary equilibria, including some that display deterministic cyclic and chaotic dynamics. There are also stochastic (sunspot) equilibria, in which credit conditions change randomly over time, even though fundamentals are deterministic and stationary. We show this can occur when the terms of trade are determined by Walrasian pricing or by Nash bargaining. The results illustrate how it is possible to generate equilibria with credit cycles (crunches, freezes, crises) in theory, and as recently observed in actual economies.